Strategy of civic education teachers in building awareness and legal compliance for the younger generation - Kurniyawan, Handi; Tanshzil, Sri Wahyuni (Indonesian Journal of Social Sciences, 2024)
The role of civic education teachers is profoundly strategic in fostering awareness and legal compliance among students. That is because civic education holds a mission and purpose to shape intelligent and virtuous citizens. One of the indicators of a good citizen is one who abides by and adheres to the existing legal regulations. Therefore, this research aims to examine the strategies and roles of civic education teachers in cultivating awareness and legal compliance among students, especially considering the numerous cases of legal violations involving students nowadays. The research design employed a qualitative approach, specifically descriptive research. The data collection technique involved conducting interviews with several civic education teachers from both junior high schools and senior high/vocational schools who are part of the civic education teachers association in Magelang Regency and also engaging with alumni from UNNES who have teaching experience. The findings of this study indicate that the strategies and roles of civic education teachers in fostering awareness and legal compliance among students involve conducting activities such as socialization, mentoring and supervision, setting examples, motivation and habituation, and collaborating with relevant stakeholders. Thus, the various strategies implemented by several civic education teachers are expected to be able to create smart and good citizens by enhancing legal awareness and compliance, especially among students (younger generation), which will subsequently have an impact on improving the quality of human resources in a country, especially in Indonesia.